Respuesta :
Answer:
The missing pieces should be after line 3.
9/4 = (x - 3)^2
<=> (3/2)^2 = (x - 3)^2
<=> x - 3 = 3/2 or x - 3 = -3/2
<=> x = 3 + 3/2 or x = 3 - 3/2
<=> x = 9/2 or x = 3/2
Hope this helps!
:)
Answer:
I think the missing steps are:
[tex]\frac{3}{2}=x-3[/tex]
and
[tex]\frac{9}{2}=x[/tex]
Step-by-step explanation:
[tex]-27=4x^2-24x[/tex]
First, factor 4 to make isolate [tex]x^2[/tex]
[tex]-27=4(x^2-6x)[/tex]
Now, divide by 4.
[tex]-\frac{27}{4}=x^2-6x[/tex]
Complete the square by adding [tex](\frac{b}{2})^2[/tex]
[tex](\frac{b}{2})^2-\frac{27}{4}=x^2-6x+ (\frac{b}{2})^2[/tex]
[tex](\frac{6}{2})^2-\frac{27}{4}=x^2-6x+ (\frac{6}{2})^2[/tex]
[tex](3)^2-\frac{27}{4}=x^2-6x+ (3)^2[/tex]
[tex]9-\frac{27}{4}=x^2-6x+9[/tex]
Solve the difference.
[tex]\frac{9*4-27}{4}=x^2-6x+9[/tex]
[tex]\frac{36-27}{4}=x^2-6x+9 \\\frac{9}{4}=x^2-6x+9[/tex]
Factor the equation.
[tex]\frac{9}{4}=(x-3)(x-3)[/tex]
Rewrite it;
[tex]\frac{9}{4}=(x-3)^2[/tex]
Extract the square root.
[tex]\sqrt{\frac{9}{4} }=x-3[/tex]
Take the square root of 9 and 4.
[tex]\frac{3}{2}=x-3[/tex]
Add 3.
[tex]\frac{3}{2}+3=x[/tex]
Do the sum
[tex]\frac{3+2*3}{2}=x\\\frac{3+6}{2}=x\\\frac{9}{2}=x[/tex]